Adult Neurogenesis and the Promise of Adult Neural Stem Cells. (June 2019) - Ghosh, Hiyaa S
The adult brain, even though largely postmitotic, is now known to have dividing cells that can make both glia and neurons. Of these, the precursor cells that have the potential to make new neurons in the adult brain have attracted great attention from researchers, anticipating their therapeutic potential for neurodegenerative conditions. In this review, I will focus on adult neurogenesis, from the perspective of the overall neurogenic potential in the adult brain, current understanding of the 'adult neural stem cell', and the importance of niche as a decisive factor for neurogenesis under homeostasis and pathologic conditions.